Maintaining Optimal Mammary Gland Health and Prevention of Mastitis - Zigo, František; Vasil', Milan; Ondrašovičová, Silvia; Výrostková, Jana; Bujok, Jolanta; Pecka-Kielb, Ewa (Frontiers in Veterinary Science, 2021)
In dairy industry, quality of produced milk must be more important than quantity without a high somatic cells count (SCC) or pathogens causing mastitis of dairy cows and consumer diseases. Preserving the good health of dairy cows is a daily challenge for all involved in primary milk production. Despite the increasing level of technological support and veterinary measures, inflammation of the mammary gland - mastitis, is still one of the main health problems and reasons for economic losses faced by cow farmers. The mammary gland of high-yielding dairy cows requires making the right decisions and enforcing the proper measures aimed at minimizing external and internal factors that increase the risk of intramammary infection. Due to the polyfactorial nature of mastitis related to its reduction, the effectiveness of commonly used antimastitis methods tends to be limited and therefore it is necessary to find the areas of risk in udder health programs and monitoring systems. Only by implementing of complete udder health programs should be accompanied by research efforts to further development these complete udder health control. The present review analyses the current knowledge dealing with damping and prevention of mastitis include SCC control, proper nutrition, housing and management, milking and drying as practiced in dairy farming conditions. This information may help to improve the health of the mammary gland and the welfare of the dairy cows as well as the production of safe milk for consumers.